2003
DOI: 10.1080/15428110308984826
|View full text |Cite
|
Sign up to set email alerts
|

Construction Work Practices and Conditions Improved After 2-Years' Participation in the HomeSafe Pilot Program

Abstract: This study reevaluated changes in job-site safety audit scores for a cohort of residential construction workers that had protracted exposure to the HomeSafe pilot program for 2(1/2) years. The investigation was a repeated measure of a cohort study underway in the six-county metro area of Denver, Colo. The larger study was a longitudinal, quasi-experimental design with a cohort of residential construction workers within the HomeSafe strategic partnership between Occupational Safety and Health Administration Reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…[16,17] A recent comprehensive review concluded that safety education and training is as an integral component to improved construction safety. [18] There is empirical evidence that occupational health and safety training increases worker knowledge, [19] improves safety behaviors, [15,20,21] and decreases workers' compensation claims among construction workers. [22,23] Two recent meta-analyses found that high engagement safety training promotes knowledge and skill acquisition [19] and has a greater impact than low engagement methods [15].…”
Section: Discussionmentioning
confidence: 99%
“…[16,17] A recent comprehensive review concluded that safety education and training is as an integral component to improved construction safety. [18] There is empirical evidence that occupational health and safety training increases worker knowledge, [19] improves safety behaviors, [15,20,21] and decreases workers' compensation claims among construction workers. [22,23] Two recent meta-analyses found that high engagement safety training promotes knowledge and skill acquisition [19] and has a greater impact than low engagement methods [15].…”
Section: Discussionmentioning
confidence: 99%
“…Authors, Sample Sizes, Data Collection Methods, Assessment Factors, Retrieved Data (Pre, Post, Control, Treatment), and Effectiveness of Selected Studies of Traditional Tools 18% (Spangenberg et al, 2002) Not Mentioned Supervisor-report (Injury Register) Injury Rate Reduction 25% reduction 25% (Gilkey et al, 2003) Self-report (Questionnaire) Behaviour Alteration 71.8% 76.8% 5% (Darragh et al, 2004) Not Mentioned Supervisor-report (Injury Register) Injury Rate Reduction 1,478 injuries in 16,946,918 hours 493 injuries in 6,706,046 hours 15.5% (Hong et al, 2006) Self-report (Questionnaire) Behaviour Alteration 50% 57% 7% (Kerr et al, 2007) Self-report (Questionnaire) Behaviour Alteration 42% 50% 8% (Neitzel et al, 2008) Self-report (Questionnaire) Behaviour Alteration 29.2% 57.1% 27.9% (Bena et al, 2009) Supervisor-report (Injury Register) Injury Rate Reduction 6% reduction 6% (Sokas et al, 2009) Self As can be seen from Table 2, almost all of the selected studies indicated the size of the samples included in their experiments, excepting two studies in which no such information was provided (Darragh et al, 2004;Spangenberg et al, 2002). The sample size varied greatly among the selected studies, ranging from 23 (Neitzel et al, 2008) to 2795 workers (Bena et al, 2009) (Column 'Sample Sizes', Table 2).…”
Section: Tablementioning
confidence: 99%
“…14 Leading indicators are often measured on construction sites through the industry practice of walk-through safety inspections. [15][16][17][18][19][20] These safety audits include measures of both the controls in place and the uncontrolled hazards, as it is acknowledged that an overall worksite safety assessment should include metrics of both safe and unsafe work conditions. 21 However, while some anecdotal evidence exists from the field, we were not able to find rigorous studies in the existing scientific literature that describe the mechanics of such a program or test its effectiveness in changing safety conditions and injury rates.…”
Section: Introductionmentioning
confidence: 99%